Working with animals - Ewing, Susan M. (Career files., 2018)
Explores a range of jobs that work with animals, surveying what people do in each job, where they work, the tools they use, and each job's average salary. Includes color photographs, sidebars, statistics, reflection questions, a glossary, and further resources.